90 Computed Tomography (CT) Angiography Planning Identifies the Target Vessel for Optimum Infarct Location and Improves Clinical Outcome in Alcohol Septal Ablation (ASA) for Hypertrophic Obstructive Cardiomyopathy. (6th June 2015) - Cooper, Robert; Binukrishnan, Sukumaran; Shahzad, Adeel; Stables, Rodney; Hasleton, Jonathan
Abstract : Background: Septal reduction is required for HOCM patients with severe LVOT gradients and symptoms refractory to medications. ASA is established in HOCM. ASA is ineffective in 20–30%: inaccurate infarct and inability to identify an appropriate septal vessel for alcohol contribute. We report results of a new technique to characterise septal vascular anatomy with CT prior to ASA. Methods: Systolic images identify SAM-septal contact area as target myocardium (Figure 1 ; panel A). The target myocardium is analysed for septal vessels in diastole (F1; panel B). The course and origin of identified vessels are characterised. Other epicardial arteries are assessed for vessels tracking towards target myocardium. Those with supply to other territories are dismissed. The target septal (s) are labelled and a 3D CT angiogram is constructed (F1; panels C-H, invasive angiogram provided for comparison). This can be rotated to remove foreshortening and overlap to define the optimum angiographic projections for the lab. Alcohol is injected into the target vessel as identified by CT. Results: CT can identify septal arteries with branching to right and left ventricular septum. Myocardial contrast injection into the ostium localises to RV due to lower pressures. Sub-selective injection into LV branch localises to target myocardium. 20 patients have received alcohol to target septal artery with follow up ¡Ý6 months (mean 375 (¡À137) days). One patient underwent two procedures. CT guided subselective injection to a branch of a septal from the LAD in 16/20 cases. The septal vessel originated from the Cx in 2/20 cases. Traditional methods were used in 2/20. For those with a resting gradient ¡Ý50 mmHg (n = 12) the mean gradient improved from 98 (IQR 89–111) mmHg to 14 (IQR 8.50–22) (p = 0.003). In those with a provoked gradient (n = 8) we saw an improvement from 82 (IQR73–108) mmHg to 22.(IQR16–3) (p = 0.007) mmHg. SAM improved in 18/20 patients. Symptoms of dyspnoea improved in 18/20 (one patient developed pulmonary fibrosis), mean NYHA improved from 2.85 (¡À0.11) to 1.45 (¡À0.39) (p < 0.0001. Predicted peak VO2 improved from 79.1 (¡À14.01)% to 91.6 (¡À12.02). Exercise time on cycle ergometer increased from 715.59 (¡À252.35) to 837.35 (¡À265.10)s (p < 0.0001). Quality of life assessed by EQ5D-5L improved in all. 75 patients were treated with traditional methods prior to CT. Success at first procedure is greater with CT guidance, 17/20 vs 50/75 (p = 0.02). 9/20 had CMR with target septum LV endocardial infarct in all (Figure 2 ). Incidence of RBBB reduced from 62% to 13% (p = 0.0004). This suggests more localised infarction to target LV (rather than RV) myocardium. Conclusions: CT angiography has changed our approach to ASA. This refined approach improves control and location of infarct. This is translating into greater success in treating LVOT gradients at the first procedure and has potential to have a greater impact on patient symptoms.